2022
DOI: 10.1155/2022/3918045
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Burden in China during 1990–2019: Analysis of the Global Burden of Disease

Abstract: This study reports the risk factors, trends, and burden of cancer in China from 1990 to 2019 from the Global Burden of Diseases. The incidence, mortality, and DALY of all cancers in China for the past 30 years were analyzed. In 2019, the age-standardized rates (ASRs) of cancer incidence, mortality, and DALY in China were 232.42/100 000, 136.72/100 000, and 3288.22/100 000, respectively. The five cancers with the highest age-standardized incidence rates were lung, stomach, colorectal, breast, and prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Authoritative research estimates that breast cancer has become the most prevalent cancer type among female cancer patients in the United States, and death also ranks second among female cancer-related death types, with a true proportion of 15% in 2022 ( 33 ). According to the latest data released by the National Cancer Center, the incidence of breast cancer in China is 7.11%, and the mortality rate is 2.81%, ranking fifth and seventh, respectively ( 34 ). Based on the above statistical results, breast cancer is a serious public health issue in current society and needs to be given great attention.…”
Section: Role and Mechanism Of Tmem88 In Malignant Tumorsmentioning
confidence: 99%
“…Authoritative research estimates that breast cancer has become the most prevalent cancer type among female cancer patients in the United States, and death also ranks second among female cancer-related death types, with a true proportion of 15% in 2022 ( 33 ). According to the latest data released by the National Cancer Center, the incidence of breast cancer in China is 7.11%, and the mortality rate is 2.81%, ranking fifth and seventh, respectively ( 34 ). Based on the above statistical results, breast cancer is a serious public health issue in current society and needs to be given great attention.…”
Section: Role and Mechanism Of Tmem88 In Malignant Tumorsmentioning
confidence: 99%
“…In China, the prevalence of cancer is rising, 1,2 with the overall incidence increasing by 169% from 1990 to 2019. 3 Besides the most attributable factor for cancer-aging, 4 cancer initiation and development are also influenced by inherited and environmental factors, with the environment playing a significant role in leading to sporadic cancer. 5 Instead of concentrating on inherited risk factors, which are difficult to change, cancer prevention should focus on modifiable factors, such as lifestyle, infectious agents, and air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of cancer is rising, 1,2 with the overall incidence increasing by 169% from 1990 to 2019 3 . Besides the most attributable factor for cancer—aging, 4 cancer initiation and development are also influenced by inherited and environmental factors, with the environment playing a significant role in leading to sporadic cancer 5 .…”
Section: Introductionmentioning
confidence: 99%
“…But the conclusions of their causal relationships remain inconclusive. The association of drinking with CRC risk is controversial in the literature (1,2,(7)(8)(9)(10)(11)(12)(13)(14)(15): Some studies have found drinking is associated with increase in CRC risk (1,(7)(8)(9)(10)(11)(12); some have reported drinking beer is associated with decrease in CRC risk (13); and some have reported no association between them (14,15). Drinking prevalence is going up over time and signi cantly different in gender, age and city in China (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%